Association between post-orthodontic treatment gingival margin alterations and symphysis dimensions - Closs, Luciane Quadrado; Bortolini, Leonardo F; Santos-Pinto, Ary dos [UNESP]; Rösing, Cassiano Kuchenbecker (My University, 2014)
Orthodontic therapy is known to be associated with the development of gingival recession. Several factors may be involved in the causal chain of this outcome, including anatomical and behavioral aspects. Among the anatomical aspects, the dimensions of the mandibular symphysis could play a predisposing role. This study evaluated the relationship between the mandibular symphysis dimensions prior to orthodontic therapy and the development of gingival recessions on the lower incisors and cuspids. Records from 189 orthodontically treated adolescents were evaluated, including radiographs, casts and intra-oral photographs. Symphysis dimensions were assessed by cephalograms. Gingival margin alterations were determined in photographs and cast models. Association between gingival margin alterations and symphysis dimensions was tested by chi-square (α=0.05). Occurrence of gingival recession increased after orthodontic therapy. No association was observed on average of symphysis dimensions and the occurrence of gingival recessions. It may be concluded that pretreatment symphysis dimensions may not be used as predictors of gingival recession after orthodontic therapy.

Sabe-se que o tratamento ortodontico esta associado com o desenvolvimento de recessao gengival. Varios fatores podem estar envolvidos na cadeia causal deste desfecho, incluindo aspectos anatomicos e comportamentais. Dentre os aspectos anatomicos, as dimensoes da sinfise mandibular poderia ter um papel predisponente. O presente estudo avaliou a relacao entre as dimensoes da sinfise mandibular previas ao tratamento ortodontico e o desenvolvimento de recessoes gengivais nos incisivos e caninos inferiores. Prontuarios de 189 adolescentes tratados ortodonticamente foram avaliados, incluindo radiografias, modelos e fotografias intra-orais. Dimensoes da sinfise foram determinadas em cefalogramas. Alteracoes da margem gengival foram observadas em fotografias e modelos. Associacoes entre alteracoes da margem gengival e dimensoes da sinfise foram testadas por qui-quadrado (α=0.05). A ocorrencia de recessao gengival aumentou apos tratamento ortodontico. Nao foi observada associacao entre as medidas medias de sinfise e a ocorrencia de recessoes gengivais. Podese concluir que as dimensoes da sinfise pre-tratamento ortodontico nao podem ser usadas como preditores de recessao gengival pos-tratamento ortodontico.
Keywords: Gingival Recession; Orthodontics; Adolescent; Periodontia; Margem gengival; Sínfise Mandibular